Using quantitative tools to measure gender differences within value chains - Madrigal, Lucia; Torero, Máximo (International Food Policy Research Institute, 2016)
Chapter 14 (Madrigal and Torero) sheds light on an important issue that is not captured by any of the previous approaches: Most value-chain impact evaluations fail to look at effects disaggregated by gender. This is an important oversight, because in most value chains men and women play different roles, and failure to account for gender in a randomized controlled trial, quasi-experimental, or participatory intervention may significantly alter the results of these studies. To resolve this gap in the literature, the authors focus on several tools and metrics to incorporate gender in value-chain impact evaluations. The Oaxaca Blinder decomposition analysis allows for proper measurement of wage gaps between men and women by controlling for other observable variables; the Duncan Index and Access to Work Equality Index measure occupational segregation and differential access to employment.